2008
DOI: 10.1007/978-1-4020-8811-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition Specificity of anti-3-nitrotyrosine Antibodies Revealed by Affinity-Mass Spectrometry and Immunoanalytical Methods

Abstract: Nitration of tyrosine residues in proteins has been mainly characterised by immunoanalytical methods using anti-3-nitrotyrosine antibodies, and nitration sites and sequences have been hitherto identified only in a few cases using mass spectrometric methods. Immuno-analytical methods frequently suffer from low and poorly characterised detection specificity of antinitrotyrosine antibodies, while mass spectrometric methods for identification of Tyrosine nitration may be hampered by low levels of modification, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The principle of this approach is analogous to a general, previously developed epitope extraction-MS method for identification of antibody-epitopes, in which a protein antigen is digested in solution and the proteolytic peptide mixture presented to the affinity column [32,33]. The 3-NTantibody-peptide(s) complex is allowed to form, and nonbinding peptides remaining in solution are removed by washing and analyzed by mass spectrometry as a supernatant fraction.…”
Section: Proteolytic Affinity-mass Spectrometry Approach For Identifimentioning
confidence: 99%
See 4 more Smart Citations
“…The principle of this approach is analogous to a general, previously developed epitope extraction-MS method for identification of antibody-epitopes, in which a protein antigen is digested in solution and the proteolytic peptide mixture presented to the affinity column [32,33]. The 3-NTantibody-peptide(s) complex is allowed to form, and nonbinding peptides remaining in solution are removed by washing and analyzed by mass spectrometry as a supernatant fraction.…”
Section: Proteolytic Affinity-mass Spectrometry Approach For Identifimentioning
confidence: 99%
“…In an analogous manner, application of the proteolytic affinity-MS approach to ECP provided the identification of a single nitration site in the proteolytic peptide obtained by trypsin digestion, ECP( 23 CTIAMRAINNY(NO 2 )R 34 ) nitrated at Tyr 33 . The uncleaved Arg 28 residue suggested that the proteolytic resistance at this residue near the Tyr 33 residue might be due to the nitration, since in non-nitrated ECP the same arginine residue was cleaved by trypsin; the observation that proteolytic cleavage is affected by a nearby Tyr-nitration site has been made in several studies on protein Eosinophil proteins were isolated from four patients with hypereosinophilia and elevated eosinophils, using a previously described protocol [36].…”
Section: Proteolytic Affinity-mass Spectrometry Approach For Identifimentioning
confidence: 99%
See 3 more Smart Citations